ChemInform Abstract: Reversible CO2 Absorption by the 6H Perovskite Ba4Sb2O9. Issue 10 (11th March 2014) - Dunstan, Matthew T.; Liu, Wen; Pavan, Adriano F.; Kimpton, Justin A.; Ling, Chris D.; Scott, Stuart A.; Dennis, John S.; Grey, Clare P.
Abstract Polycrystalline Ba4Sb2O9 is prepared by calcination of a stoichiometric mixture of BaCO3 and Sb2O3 (1273 K, 2 d).